Validation of Automated Respiratory Event Scoring in Type 3 Home Sleep Apnea Testing - Shiroshita N; Obata R; Kawana F; Kato M; Sato A; Ishiwata S; Yatsu S; Matsumoto H; Shitara J; Murata A; Shimizu M; Kato T; et al. (Nature and Science of Sleep)
Nanako Shiroshita,1,* Ryoko Obata,1,2,* Fusae Kawana,1 Mitsue Kato,1 Akihiro Sato,3 Sayaki Ishiwata,3 Shoichiro Yatsu,3 Hiroki Matsumoto,3,4 Jun Shitara,3 Azusa Murata,3 Megumi Shimizu,3 Takao Kato,3,4 Shoko Suda,1,3,4 Yasuhiro Tomita,3– 5 Masaru Hiki,3 Ryo Naito,3,4 Takatoshi Kasai1,3,4 1Cardiovascular Respiratory Sleep Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 2Philips Japan, Tokyo, Japan; 3Department of Cardiovascular Biology and Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 4Sleep and Sleep-Disordered Breathing Center, Juntendo University Hospital, Tokyo, Japan; 5Sleep Center, Toranomon Hospital, Tokyo, Japan*These authors contributed equally to this workCorrespondence: Takatoshi Kasai, Department of Cardiovascular Biology and Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan, Tel +81-3-3813-3111, Fax +81-3-5689-0627, Email kasai-t@mx6.nisiq.netPurpose: Home sleep apnea tests (HSATs) using polygraphy devices are becoming increasingly important for evaluating obstructive sleep apnea. Alice NightOne, a widely used polygraphy device, includes automatic scoring software; however, more reliable scoring results can be provided by incorporating advanced algorithmic systems like Somnolyzer. Despite this, the accuracy of automatic scoring of this polygraphy device using such applications has not been specifically investigated. Thus, in this study, we aimed to compare the respiratory event indices (REIs) obtained via automatic scoring versus manual scoring.Patients and Methods: Data of eligible patients who underwent HSAT with this polygraphy device were retrospectively analyzed using the following three methods: 1) manual scoring; 2) default automatic scoring of the analysis software; and 3) automatic scoring with the Somnolyzer system. The REIs were calculated using these three methods and expressed as mREI, aREI, and sREI, respectively. Correlations and agreements between the aREI, sREI, and mREI were assessed.Results: Data from 20 patients were analyzed. The mean mREI, aREI, and sREI were 14.7± 13.3, 13.7± 11.8, and 14.3± 13.4 events/h, respectively. A strong correlation was found between aREI and mREI (coefficient, 0.976; P< 0.01), with a mean difference between them of 1.0 and a limit of agreement of − 5.3 to 7.3. The correlation between sREI and mREI was more prominent (coefficient, 0.996; P< 0.001); their mean difference was 0.1, with a limit of agreement of − 2.1 to 2.9.Conclusion: Automatic scoring of REI using this polygraphy device showed good correlation and agreement with manual scoring. The favorable correlation and agreement were more pronounced with the Somnolyzer system.Keywords: apnea, home sleep test, hypopnea, sleep apnea, sleep study